Home Beyond the House Transformation of Life, Place, and Tradition in Rural China (Taylor & Francis, 2023)
China; Home; House; Life; Place; Rural; Tradition; Transformation
English
Keywords: Architecture: residential and domestic buildings; Architecture; Landscape architecture and design; China; Home; House; Life; Place; Rural; Tradition; Transformation